High / low-temperature-resistant and wear-resistant lubricating oil and preparation method thereof

By using composite antiwear agents and specific compounds in lubricating oil to form a bridge structure, the problem of insufficient friction and wear performance of traditional lubricating oil under extreme pressure conditions is solved, high and low temperature wear resistance is achieved, and the thermal stability and low temperature flowability of lubricating oil are improved.

CN119842433APending Publication Date: 2025-04-18HENAN OVERVIEW IND CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411770643.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

Traditional lubricating oils have insufficient friction and wear performance under extreme pressure conditions, and commonly used esterification catalysts have side reactions and equipment corrosion problems, making it difficult to meet the requirements of modern production processes.

Method used

Compound anti-wear agent is used to make composite particles from zirconium oxychloride and manganese sulfate through sol-gel method, and mixed with methylphenyl dimethoxysilane, combined with 1,2,4,5-tetrahydroxybenzene and 2,7-naphthalene dicarboxylic acid to form a bridge structure to prepare high and low temperature resistance lubricating oil.

Benefits of technology

It realizes reducing the viscosity change range in high and low temperature environments, extending the service life of lubricant oil, improving wear resistance, and maintaining the thermal stability and low temperature flowability of lubricant oil.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005170183000000061
    Figure BDA0005170183000000061
  • Figure BDA0005170183000000071
    Figure BDA0005170183000000071
Patent Text Reader

Abstract

The invention discloses high and low temperature-resistant and wear-resistant lubricating oil and a preparation method thereof, and relates to the technical field of lubricating oil. According to the invention, 1, 2, 4, 5-tetrahydroxybenzene and 2, 7-naphthalenedicarboxylic acid react under the catalysis of the composite anti-wear agent to form a bridging structure, and a benzene ring is introduced to enhance the temperature resistance; and then a diester structure is formed with isotridecanol, so that a main carbon chain is prolonged, the number of branched chains and ester bases is increased, the viscosity-temperature property, low-temperature fluidity and wear resistance are improved, meanwhile, waxy substances are prevented from being crystallized, and the low-temperature fluidity is guaranteed. Wherein the composite anti-wear agent is tin-manganese composite particles prepared from zirconium oxychloride and manganese sulfate through a sol-gel method, so that the specific surface area is increased, the synthesis conversion of base oil is promoted, a film can be formed on the metal surface to reduce wear, free radicals are captured, and the service life is prolonged; then adsorbing with methylphenyldimethoxysilane through Van der Waals force to generate steric hindrance, helping particles to disperse stably, introducing Si-O bonds, and strengthening the high-temperature and low-temperature resistant effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lubricating oils, in particular to a high-low temperature resistant and wear-resistant lubricating oil and a preparation method thereof. Background Art

[0002] With the development of science and technology, many equipment parts need to be used under complex extreme pressure conditions, which will bring greater friction and wear. Therefore, higher requirements are also put forward for the performance of lubricants. It is required not only to have higher lubrication performance, but also higher extreme pressure performance and be able to withstand greater loads. In the automotive industry, the role of lubricants is particularly important. Most of the energy in the operation of the car is still used to overcome friction and wear, and only a small part of the energy is used for the normal operation of the car. If the automotive industry wants to achieve faster and better development, it must first solve the problem of friction and wear. Lubricants, as the "blood" of the car, are the most effective methods and measures to solve the friction and wear of the car. Traditional lubricants are limited in lubrication performance and most of them contain elements such as P, S and Cl, which are easy to corrode the surface of mechanical parts and pollute the environment. They cannot meet the requirements of modern production processes. Therefore, it is particularly important to develop a new type of green lubricant with excellent anti-wear and friction reduction properties.

[0003] Ester base oil can take into account high performance, multi-function and environmental protection, and the viscosity is easy to control, so it can be used as the base oil of high-performance lubricating oil. Although ester base oil itself is an environmentally friendly high-performance base oil, its commonly used esterification catalysts include concentrated sulfuric acid, p-toluenesulfonic acid, titanate, zirconate and cation exchange resin. The strong acidity and strong oxidizing property of concentrated sulfuric acid will cause a variety of side reactions, resulting in excessive sulfur content in the product, an increase in non-ideal components, a darkening of the oil color and equipment corrosion, which will lead to subsequent problems such as difficulty in refining, large wastewater discharge and low product yield, as well as difficulty in reconciling the contradiction between low residue and high catalytic activity. In addition, most catalysts need to be separated and reused, which increases the difficulty of separation and the preparation cost. Summary of the invention

[0004] The purpose of the present invention is to provide a high and low temperature resistant anti-wear lubricating oil and a preparation method thereof, so as to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a high and low temperature resistant and wear-resistant lubricating oil, wherein the high and low temperature resistant and wear-resistant lubricating oil is prepared by synthesizing a modified lubricating oil catalyzed by a composite anti-wear agent.

[0006] Furthermore, the composite anti-wear agent is prepared by preparing composite particles from zirconium oxychloride and manganese sulfate by a sol-gel method, and then mixing the composite particles with methylphenyldimethoxysilane.

[0007] Furthermore, the modified lubricating oil mainly comprises 1,2,4,5-tetrahydroxybenzene, 2,7-naphthalene dicarboxylic acid and isotridecanol.

[0008] Furthermore, a method for preparing a high and low temperature resistant and wear-resistant lubricating oil comprises the following preparation steps:

[0009] (1) 20 to 30 parts of zirconium oxychloride, 15 to 25 parts of manganese sulfate, and 90 to 160 parts of deionized water are mixed uniformly, and the pH value of the solution is adjusted to 9.5 to 11.5 with ethylenediamine, and the mixture is stirred at 35 to 55° C. and 120 rpm for 0.5 to 1.5 h, and then dried in an oven at 55 to 65° C. for 18 to 24 h, and then calcined in a muffle furnace at 600 to 800° C. for 2 to 3 h, and crushed into powder to obtain composite particles;

[0010] (2) dispersing 3 to 7 parts of the composite particles in 25 to 55 parts of anhydrous ethanol, ultrasonically dispersing at 80 kHz for 20 to 50 minutes, adding 12 to 28 parts of methylphenyldimethoxysilane-ethanol solution, stirring at 55 to 65° C. and 120 rpm for 12 to 16 hours, centrifuging at 5000 r / min for 8 to 14 minutes in a centrifuge, washing with anhydrous ethanol and deionized water alternately for 3 times, and drying in an oven at 45 to 55° C. for 14 to 18 hours to obtain a composite antiwear agent;

[0011] (3) Under nitrogen protection, 8 to 12 parts of 1,2,4,5-tetrahydroxybenzene and 4 to 6 parts of 2,7-naphthalene dicarboxylic acid are mixed uniformly, the temperature is raised to 155 to 175° C., 0.2 to 0.8 parts of a composite anti-wear agent are added, the mixture is reacted at 300 rpm for 0.7 to 1.5 hours, 15 to 23 parts of a 2,7-naphthalene dicarboxylic acid-isotridecanol mixed solution are added, the reaction is continued for 3.5 to 5.5 hours, and the mixture is naturally cooled to room temperature to obtain a modified lubricating oil;

[0012] (4) 94 to 106 parts of modified lubricating oil, 3 to 5 parts of dispersant, 2 to 4 parts of antioxidant, and 1 to 3 parts of defoaming agent are mixed evenly, and filtered with a filtration accuracy of 15 to 25 μm to obtain a high and low temperature resistant and wear resistant lubricating oil.

[0013] Furthermore, the particle size of the powder after crushing in step (1) is 200 nm.

[0014] Furthermore, the content of methylphenyldimethoxysilane in the methylphenyldimethoxysilane-ethanol solution in step (2) is 1 wt%.

[0015] Furthermore, in the 2,7-naphthalene dicarboxylic acid-isotridecanol mixed solution of step (3), the molar ratio of 2,7-naphthalene dicarboxylic acid to isotridecanol is 1:1.

[0016] Furthermore, the dispersant in step (4) is any one of polyisobutylene succinimide, polymethacrylate, and triisopropyl borate.

[0017] Furthermore, the antioxidant in step (4) is any one of 2,6-di-tert-butyl-p-cresol and dialkyl diphenylamine.

[0018] Furthermore, the defoaming agent in step (4) is polydimethylsiloxane.

[0019] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0020] The present invention utilizes 1,2,4,5-tetrahydroxybenzene and 2,7-naphthalene dicarboxylic acid to react and combine under the catalysis of a composite anti-wear agent to form a bridge structure. In a low-temperature environment, the bridge structure can inhibit excessive curling and aggregation of molecular chains, maintain a relatively orderly arrangement between molecules, thereby reducing the increase in viscosity at low temperatures. In a high-temperature environment, it can prevent excessive stretching and breaking of molecular chains, maintain the interaction between molecules, and slow down the rate at which viscosity decreases with increasing temperature, thereby achieving high-temperature and low-temperature resistance effects. In addition, multiple benzene rings are introduced, and the symmetrical structure has a small change in the balance of intermolecular forces when the temperature changes. , making the temperature change have less effect on the lubricating oil, thereby further enhancing the high temperature and low temperature resistance; then forming a diester structure with isotridecanol, extending the length of the main carbon chain, increasing the number of side chains and ester groups, while increasing the viscosity, maintaining the viscosity-temperature performance, low temperature fluidity and high thermal stability of the lubricating oil, and introducing long chain segments at the same time, which can be adsorbed and arranged on the surface to form an effective lubricating film, reduce metal-to-metal wear, and thus improve wear resistance. On this basis, the presence of long chains can prevent the crystallization of waxy substances in the lubricating oil, so that the lubricating oil can still maintain good fluidity at lower temperatures and achieve low temperature resistance.

[0021] Secondly, the composite anti-wear agent is first prepared from zirconium oxychloride and manganese sulfate by a sol-gel method to obtain tin-manganese composite particles, thereby increasing the specific surface area of ​​the particles and improving the base oil synthesis conversion rate. At the same time, a protective film can be formed on the metal surface during the friction process to reduce direct contact and wear between metals, capture free radicals generated during the oxidation process of the lubricating oil, prevent chain reactions, and extend the service life of the lubricating oil; and then physically adsorbed on the surface of the composite particles with methylphenyldimethoxysilane under the action of van der Waals force, generating steric resistance between the composite particles, so that the composite particles can be stably dispersed in the base oil for a long time, achieving a long-term anti-wear effect, while introducing a stable Si-O bond to improve thermal stability and low-temperature fluidity, further enhancing the high and low temperature resistance effect. DETAILED DESCRIPTION

[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0023] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the high and low temperature resistant and anti-wear lubricating oil prepared in the following examples are as follows:

[0024] Wear spot diameter and four-ball bearing capacity load: Take the embodiment and comparative example of the same mass and test them according to the standard GB / T3142.

[0025] Coking quality: The same mass of the Example and the Comparative Example were taken and the coking quality was tested at 150°C for 20 h using a lubricating oil high temperature coking performance tester.

[0026] Solidification point: Take the same mass of the embodiment and the comparative example and test them according to the standard GB / T 510.

[0027] Example 1

[0028] (1) 20 parts of zirconium oxychloride, 15 parts of manganese sulfate, and 90 parts of deionized water were mixed uniformly, and the pH value of the solution was adjusted to 9.5 with ethylenediamine. After stirring at 35° C. and 120 rpm for 0.5 h, the mixture was dried in an oven at 55° C. for 18 h, and then calcined in a muffle furnace at 600° C. for 2 h, and crushed into a powder with a particle size of 200 nm to obtain composite particles;

[0029] (2) dispersing 3 parts of the composite particles in 25 parts of anhydrous ethanol, ultrasonically dispersing at 80 kHz for 20 min, adding 12 parts of a methylphenyldimethoxysilane-ethanol solution having a methylphenyldimethoxysilane content of 1 wt%, stirring at 55° C. and 120 rpm for 12 h, centrifuging at 5000 r / min for 8 min in a centrifuge, washing with anhydrous ethanol and deionized water alternately for 3 times, and drying in an oven at 45° C. for 14 h to obtain a composite antiwear agent;

[0030] (3) Under nitrogen protection, 8 parts of 1,2,4,5-tetrahydroxybenzene and 4 parts of 2,7-naphthalene dicarboxylic acid were mixed uniformly, the temperature was raised to 155° C., 0.2 parts of a composite anti-wear agent was added, the mixture was reacted at 300 rpm for 0.7 h, 15 parts of a 2,7-naphthalene dicarboxylic acid-isotridecanol mixed solution were added, the reaction was continued for 3.5 h, and the mixture was naturally cooled to room temperature to obtain a modified lubricating oil; the molar ratio of 2,7-naphthalene dicarboxylic acid to isotridecanol in the 2,7-naphthalene dicarboxylic acid-isotridecanol mixed solution was 1:1;

[0031] (4) 94 parts of modified lubricating oil, 3 parts of polyisobutylene succinimide, 2 parts of 2,6-di-tert-butyl-p-cresol, and 1 part of polydimethylsiloxane are mixed evenly, and filtered with a filtration accuracy of 15 μm to obtain a high and low temperature resistant and wear-resistant lubricating oil.

[0032] Example 2

[0033] (1) 25 parts of zirconium oxychloride, 20 parts of manganese sulfate, and 125 parts of deionized water were mixed uniformly, and the pH value of the solution was adjusted to 10.5 with ethylenediamine. After stirring at 45° C. and 120 rpm for 1 hour, the mixture was dried in an oven at 60° C. for 21 hours, and then calcined in a muffle furnace at 700° C. for 2.5 hours, and crushed into a powder with a particle size of 200 nm to obtain composite particles;

[0034] (2) dispersing 5 parts of the composite particles in 40 parts of anhydrous ethanol, ultrasonically dispersing at 80 kHz for 35 minutes, adding 20 parts of a methylphenyldimethoxysilane-ethanol solution having a methylphenyldimethoxysilane content of 1 wt%, stirring at 60° C. and 120 rpm for 14 hours, centrifuging at 5000 r / min for 11 minutes in a centrifuge, washing three times with anhydrous ethanol and deionized water alternately, and drying in an oven at 50° C. for 16 hours to obtain a composite antiwear agent;

[0035] (3) Under nitrogen protection, 10 parts of 1,2,4,5-tetrahydroxybenzene and 5 parts of 2,7-naphthalene dicarboxylic acid were mixed uniformly, the temperature was raised to 165° C., 0.5 parts of a composite anti-wear agent was added, the mixture was reacted at 300 rpm for 1.1 h, 19 parts of a 2,7-naphthalene dicarboxylic acid-isotridecanol mixed solution were added, the reaction was continued for 4.5 h, and the mixture was naturally cooled to room temperature to obtain a modified lubricating oil; the molar ratio of 2,7-naphthalene dicarboxylic acid to isotridecanol in the 2,7-naphthalene dicarboxylic acid-isotridecanol mixed solution was 1:1;

[0036] (4) 100 parts of modified lubricating oil, 4 parts of polymethacrylate, 3 parts of dialkyldiphenylamine and 2 parts of polydimethylsiloxane are mixed evenly, and filtered with a filtration accuracy of 20 μm to obtain a high and low temperature resistant and wear-resistant lubricating oil.

[0037] Example 3

[0038] (1) 30 parts of zirconium oxychloride, 25 parts of manganese sulfate, and 160 parts of deionized water were mixed uniformly, and the pH value of the solution was adjusted to 11.5 with ethylenediamine. After stirring at 55° C. and 120 rpm for 1.5 h, the mixture was dried in an oven at 65° C. for 24 h, and then calcined in a muffle furnace at 800° C. for 3 h, and crushed into a powder with a particle size of 200 nm to obtain composite particles;

[0039] (2) dispersing 7 parts of the composite particles in 55 parts of anhydrous ethanol, ultrasonically dispersing at 80 kHz for 50 min, adding 28 parts of a methylphenyldimethoxysilane-ethanol solution having a methylphenyldimethoxysilane content of 1 wt%, stirring at 65° C. and 120 rpm for 16 h, centrifuging at 5000 r / min for 14 min in a centrifuge, washing with anhydrous ethanol and deionized water alternately for 3 times, and drying in an oven at 55° C. for 18 h to obtain a composite antiwear agent;

[0040] (3) Under nitrogen protection, 12 parts of 1,2,4,5-tetrahydroxybenzene and 6 parts of 2,7-naphthalene dicarboxylic acid were mixed uniformly, the temperature was raised to 175° C., 0.8 parts of a composite anti-wear agent was added, the mixture was reacted at 300 rpm for 1.5 hours, 23 parts of a 2,7-naphthalene dicarboxylic acid-isotridecanol mixed solution were added, the reaction was continued for 5.5 hours, and the mixture was naturally cooled to room temperature to obtain a modified lubricating oil; the molar ratio of 2,7-naphthalene dicarboxylic acid to isotridecanol in the 2,7-naphthalene dicarboxylic acid-isotridecanol mixed solution was 1:1;

[0041] (4) 106 parts of modified lubricating oil, 5 parts of triisopropyl borate, 4 parts of 2,6-di-tert-butyl-p-cresol, and 3 parts of polydimethylsiloxane were mixed evenly, and filtered with a filtration accuracy of 25 μm to obtain a high and low temperature resistant and wear-resistant lubricating oil.

[0042] Comparative Example 1

[0043] The difference between Comparative Example 1 and Example 2 is that step (3) is different. Step (3) is changed to: under nitrogen protection, 5 parts of 2,7-naphthalene dicarboxylic acid and 19 parts of 2,7-naphthalene dicarboxylic acid-isotridecanol mixed solution are mixed uniformly, heated to 165° C., 0.5 parts of composite anti-wear agent are added, reacted at 300 rpm for 4.5 hours, and naturally cooled to room temperature to obtain modified lubricating oil; the molar ratio of 2,7-naphthalene dicarboxylic acid to isotridecanol in the 2,7-naphthalene dicarboxylic acid-isotridecanol mixed solution is 1:1. The remaining steps are the same as in Example 2.

[0044] Comparative Example 2

[0045] The difference between Comparative Example 2 and Example 2 is that step (3) is different. Step (3) is changed to: under nitrogen protection, 10 parts of 1,2,4,5-tetrahydroxybenzene and 19 parts of isotridecanol are mixed uniformly, heated to 165° C., 0.5 parts of composite antiwear agent are added, reacted at 300 rpm for 4.5 hours, and naturally cooled to room temperature to obtain modified lubricating oil. The remaining steps are the same as those in Example 2.

[0046] Comparative Example 3

[0047] The difference between Comparative Example 3 and Example 2 is that step (3) is different. Step (3) is changed to: under nitrogen protection, 10 parts of 1,2,4,5-tetrahydroxybenzene and 5 parts of 2,7-naphthalene dicarboxylic acid are mixed uniformly, heated to 165° C., 0.5 parts of composite anti-wear agent are added, reacted at 300 rpm for 1.1 hours, 19 parts of 2,7-naphthalene dicarboxylic acid are added, the reaction is continued for 4.5 hours, and naturally cooled to room temperature to obtain modified lubricating oil. The remaining steps are the same as those in Example 2.

[0048] Comparative Example 4

[0049] The difference between Comparative Example 4 and Example 2 is that there is no step (1), and step (2) is changed to: 5 parts of manganese dioxide are dispersed in 40 parts of anhydrous ethanol, ultrasonically dispersed at 80kHz for 35 minutes, 20 parts of methylphenyldimethoxysilane-ethanol solution with a methylphenyldimethoxysilane content of 1wt% are added, stirred at 60°C and 120rpm for 14h, placed in a centrifuge at 5000r / min for 11min, washed alternately with anhydrous ethanol and deionized water for 3 times, and dried in an oven at 50°C for 16h to obtain a composite antiwear agent. The remaining steps are the same as those in Example 2.

[0050] Comparative Example 5

[0051] The difference between Comparative Example 5 and Example 2 is that step (1) is different. Step (1) is changed to: 25 parts of zirconium oxychloride and 125 parts of deionized water are mixed uniformly, the pH value of the solution is adjusted to 10.5 with ethylenediamine, stirred at 45° C. and 120 rpm for 1 hour, dried in an oven at 60° C. for 21 hours, then calcined in a muffle furnace at 700° C. for 2.5 hours, and ground into a powder with a particle size of 200 nm to obtain composite particles. The remaining steps are the same as those in Example 2.

[0052] Comparative Example 6

[0053] The difference between Comparative Example 6 and Example 2 is that there is no step (2), and step (3) is changed to: under nitrogen protection, 10 parts of 1,2,4,5-tetrahydroxybenzene and 5 parts of 2,7-naphthalene dicarboxylic acid are mixed uniformly, heated to 165° C., 0.5 parts of composite particles are added, reacted at 300 rpm for 1.1 hours, 19 parts of 2,7-naphthalene dicarboxylic acid-isotridecanol mixed solution are added, the reaction is continued for 4.5 hours, and naturally cooled to room temperature to obtain a modified lubricating oil; the molar ratio of 2,7-naphthalene dicarboxylic acid to isotridecanol in the 2,7-naphthalene dicarboxylic acid-isotridecanol mixed solution is 1:1. The remaining steps are the same as in Example 2.

[0054] Effect example

[0055] Table 1 below shows the performance analysis results of the high and low temperature resistant and anti-wear lubricating oils of Examples 1 to 3 of the present invention and Comparative Examples 1 to 6.

[0056] Table 1

[0057]

[0058]

[0059] From the comparison of the experimental data of Examples 1, 2, and 3 with those of Comparative Examples 1 and 2, it can be found that 1,2,4,5-tetrahydroxybenzene and 2,7-naphthalene dicarboxylic acid are reacted and combined under the catalysis of the composite anti-wear agent to form a bridging structure. In a low-temperature environment, the bridging structure can inhibit excessive curling and aggregation of the molecular chain, maintain a relatively orderly arrangement between molecules, thereby reducing the increase in viscosity at low temperatures. In a high-temperature environment, it can prevent the molecular chain from overstretching and breaking, maintain the interaction between molecules, and slow down the rate at which the viscosity decreases with increasing temperature, thereby achieving high-temperature and low-temperature resistance effects. In addition, multiple benzene rings are introduced, and the symmetrical structure of the symmetrical structure has a small change in the balance of intermolecular forces when the temperature changes, so that the temperature change has little effect on the lubricating oil, thereby further enhancing the high-temperature and low-temperature resistance effect. From the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 3, it can be found that the addition of isotridecanol can form a diester structure, extend the length of the main carbon chain, increase the number of side chains and ester groups, and maintain the viscosity-temperature performance, low-temperature fluidity and high thermal stability of the lubricating oil while increasing viscosity. At the same time, the introduction of long chain segments can adsorb and arrange on the surface to form an effective lubricating film, reducing the wear between metals, thereby improving the wear resistance. On this basis, the presence of long chains can prevent the crystallization of waxy substances in the lubricating oil, so that the lubricating oil can still maintain good fluidity at a relatively low temperature and achieve low temperature resistance. From the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Examples 4 and 5, it can be found that by adding manganese dioxide and zirconium oxide composite particles, the specific surface area of ​​the particles can be increased, the synthetic conversion rate of the base oil can be improved, and at the same time, a protective film can be formed on the metal surface during the friction process, reducing the direct contact and wear between the metals, and capturing the free radicals generated during the oxidation process of the lubricating oil, preventing the chain reaction, and extending the service life of the lubricating oil. From the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 6, it can be found that methylphenyldimethoxysilane is physically adsorbed on the surface of the composite particles under the action of van der Waals force, and a spatial resistivity is generated between the composite particles, so that the composite particles can be stably dispersed in the base oil for a long time, achieving a long-term anti-wear effect, and at the same time, a stable Si-O bond is introduced to improve thermal stability and low-temperature fluidity, and further enhance the high and low temperature resistance effect.

[0060] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A high and low temperature resistant and wear-resistant lubricating oil, characterized in that: The high and low temperature resistant and wear-resistant lubricating oil is prepared by synthesizing the modified lubricating oil through catalysis of a composite anti-wear agent.

2. The high and low temperature resistant and anti-wear lubricating oil according to claim 1, characterized in that: The composite anti-wear agent is prepared by preparing composite particles from zirconium oxychloride and manganese sulfate by a sol-gel method, and then mixing the composite particles with methylphenyldimethoxysilane.

3. The high and low temperature resistant and anti-wear lubricating oil according to claim 1, characterized in that: The modified lubricating oil mainly comprises 1,2,4,5-tetrahydroxybenzene, 2,7-naphthalene dicarboxylic acid and isotridecanol.

4. A method for preparing a high and low temperature resistant and wear-resistant lubricating oil, characterized in that: The method comprises the following preparation steps: (1) 20 to 30 parts of zirconium oxychloride, 15 to 25 parts of manganese sulfate, and 90 to 160 parts of deionized water are mixed uniformly, and the pH value of the solution is adjusted to 9.5 to 11.5 with ethylenediamine, and the mixture is stirred at 35 to 55° C. and 120 rpm for 0.5 to 1.5 h, and then dried in an oven at 55 to 65° C. for 18 to 24 h, and then calcined in a muffle furnace at 600 to 800° C. for 2 to 3 h, and crushed into powder to obtain composite particles; (2) dispersing 3 to 7 parts of the composite particles in 25 to 55 parts of anhydrous ethanol, ultrasonically dispersing at 80 kHz for 20 to 50 minutes, adding 12 to 28 parts of methylphenyldimethoxysilane-ethanol solution, stirring at 55 to 65° C. and 120 rpm for 12 to 16 hours, centrifuging at 5000 r / min for 8 to 14 minutes in a centrifuge, washing with anhydrous ethanol and deionized water alternately for 3 times, and drying in an oven at 45 to 55° C. for 14 to 18 hours to obtain a composite antiwear agent; (3) Under nitrogen protection, 8 to 12 parts of 1,2,4,5-tetrahydroxybenzene and 4 to 6 parts of 2,7-naphthalene dicarboxylic acid are mixed uniformly, the temperature is raised to 155 to 175° C., 0.2 to 0.8 parts of a composite anti-wear agent are added, the mixture is reacted at 300 rpm for 0.7 to 1.5 hours, 15 to 23 parts of a 2,7-naphthalene dicarboxylic acid-isotridecanol mixed solution are added, the reaction is continued for 3.5 to 5.5 hours, and the mixture is naturally cooled to room temperature to obtain a modified lubricating oil; (4) 94 to 106 parts of modified lubricating oil, 3 to 5 parts of dispersant, 2 to 4 parts of antioxidant, and 1 to 3 parts of defoaming agent are mixed evenly, and filtered with a filtration accuracy of 15 to 25 μm to obtain a high and low temperature resistant and wear resistant lubricating oil.

5. The method for preparing a high and low temperature resistant and anti-wear lubricating oil according to claim 4, characterized in that: The particle size of the powder after crushing in step (1) is 200 nm.

6. The method for preparing a high and low temperature resistant and anti-wear lubricating oil according to claim 4, characterized in that: The content of methylphenyldimethoxysilane in the methylphenyldimethoxysilane-ethanol solution in step (2) is 1wt%.

7. The method for preparing a high and low temperature resistant and anti-wear lubricating oil according to claim 4, characterized in that: The molar ratio of 2,7-naphthalene dicarboxylic acid to isotridecanol in the 2,7-naphthalene dicarboxylic acid-isotridecanol mixed solution of step (3) is 1:

1.

8. The method for preparing a high and low temperature resistant and anti-wear lubricating oil according to claim 4, characterized in that: The dispersant in step (4) is any one of polyisobutylene succinimide, polymethacrylate, and triisopropyl borate.

9. The method for preparing a high and low temperature resistant and anti-wear lubricating oil according to claim 4, characterized in that: The antioxidant in step (4) is any one of 2,6-di-tert-butyl-p-cresol and dialkyl diphenylamine.

10. The method for preparing a high-low temperature resistant and anti-wear lubricating oil according to claim 4, characterized in that: The defoaming agent in step (4) is polydimethylsiloxane.